A classification and review of timed Markov models of manufacturing systems. (February 2019) - Papadopoulos, Chrissoleon T.; Li, Jingshan; O'Kelly, Michael E.J.
Highlights: Classification and review of Markov models of manufacturing systems. Classification and review of other timed models of various types of manufacturing systems. Numerical solution methods of large Markov chains and specific software tools. Provision of specific directions for further research. Abstract: Many problems in manufacturing systems can be formulated via Markov stochastic modeling. This paper gives a review and classification of timed models of manufacturing systems with particular emphasis on Markov models. As the associated Markov chains of even small systems are characterized by the well-known state explosion or largeness problem, the review continues on with the models and methods for the numerical solutions of large Markov chains. In addition, the software tools are summarized. Finally, the paper provides some challenges and directions for further research on the modeling of manufacturing systems.